Contribuição ao conhecimento químico das plantas do Nordeste do Brasil: estudo bioguiado por CLAE de Turnera ulmifolia Linn. e de Pterodon polygalaeflorus Benth. e estudo dos constituintes voláteis de Pluchea quitoc DC - Cordeiro, Francisca Cristina Vasconcelos (2002)
This work describes the chemical study monitored by denaturizing tests of deoxyribonucleic acid (DNA), using high efficiency liquid chromatography (HPLC), of Turnera ulmifolia L. (Turneraceae) and Pterodon polygalaeflorus Benth (Leguminosae), known popularly as Chanana and Sucupira respectively. The chemical composition of Pluchea quitoc DC (Compositae) essential oil, better known as Madrecravo, was also studied. [...]